Periodontite agressiva: abordagens diagnósticas, terapêuticas e preventivas - Casarin, Renato Corrêa Viana [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
Aggressive periodontitis (AgP) has a great impact on the quality of life of the individuals affected by this pathology. It has early onset, rapid and severe progression, poor response to therapeutic approaches and is associated with high rates of tooth loss. AgP presents a complex pathogenesis - the onset and progression of the disease, as well as the response to treatment, are determined by the microbiota, the host's immune-inflammatory pattern and the therapeutic approaches adopted. However, none of these factors is fully elucidated in the literature. Thus, 9 studies were compiled focusing on understanding etiological, therapeutic and preventive factors of this disease. In the first study, 200 Brazilian individuals with AgP were evaluated for the presence of genetic polymorphisms of the rs1537415 (GLT6D1), rs6667202 (IL10) and rs1333048 (ANRIL). These polymorphisms have already been described in other populations also affected by AgP. It was observed that the rare C allele of the IL-10 gene presented a lower frequency (23.5%) in the AgP population compared to subjects with chronic (n=190, 30.3%) and healthy periodontitis (n=196; 34.2%), indicating a protective character of this polymorphism for the occurrence of AgP. However, high-throughput approaches could indicate new polymorphisms related to this disease. In the second chapter, exomic analysis was performed using a familiar filtering approach, confirmed in a population-based study, in familiar nuclei with AgP. After analysis of the exome and validation by real-time PCR, functional and in silico analysis, it was possible to identify the indel in the GPRC6A gene (p.Tyr775LeufsTer776) associated with AgP, presenting higher frequency in the affected population, indicating a new target to understand its occurrence. However, genetic alterations can affect the functioning of the protection systems and homeostasis, leading to the occurrence of the disease. Thus, in order to identify constitutive...

A periodontite agressiva (PA) tem grande impacto na qualidade de vida dos indivíduos acometidos por esta patologia. Possui início precoce, rápida e severa progressão, pobre resposta as abordagens terapêuticas e é associada a altas taxas de perda dentária. De patogênese complexa, o início e progressão da doença e a resposta ao tratamento são determinadas pela microbiota, resposta imune-inflamatória do hospedeiro e pelas diferentes abordagens terapêuticas adotadas. Contudo, nenhum desses fatores está totalmente elucidado na literatura. Dessa forma, foram compilados 9 estudos que focaram entender fatores etiológicos, terapêuticos e preventivos dessa doença. No primeiro estudo, foram avaliados 200 indivíduos brasileiros portadores de PA quanto a presença de polimorfismos genéticos dos genes rs1537415 (GLT6D1), rs6667202 (IL10) e rs1333048 (ANRIL), polimorfismos já descritos em outras populações também afetadas pela PA. Foi observado que o alelo raro C do gene da IL-10 apresentou menor frequência (23,5%) na população PA comparado com sujeitos com periodontite crônica (n=190; 30,3%) e saudáveis (n=196; 34,2%), indicando um caráter protetor desse polimorfismo para a ocorrência da PA. Contudo, abordagens mais amplas poderiam indicar novos polimorfismos relacionados a essa doença. No segundo capítulo foi realizado uma análise exômica com um protocolo de filtragem familiar, confirmado em estudo populacional, em núcleos familiares com PA. Após a análise do exoma e validação por PCR-real time, análise funcional e in silico, foi possível identificar o indel no gene GPRC6A (p.Tyr775LeufsTer776), com a PA, o qual apresentou maior frequência na população afetada, indicando um novo foco para avaliar a ocorrência da mesma. Entretanto, alterações genéticas podem afetar o funcionamento dos sistemas de proteção e homeostase, levando a ocorrência da doença. Assim, no intuito de identificar alterações...
Keywords: Periodontite agressiva; Etiologia Etiologia; Placa dentária; Antibacterianos; Genética